2013
DOI: 10.1159/000353148
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Liquid-Based Preparation in the Evaluation of Endometrial Cytology

Abstract: Objective: Liquid-based preparation (LBP) of the endometrial lesions is an important diagnostic tool for a variety of endometrial abnormalities because of its simplicity and high quali-quantitative diagnostic yield. We aimed to investigate the LBP method for endometrial cytology to evaluate both benign and abnormal endometrial lesions. Study Design: LBP is a semiautomated methodology that has recently become widely available and has gained popularity as a method of collecting and processing both gynecologic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 58 publications
(94 reference statements)
3
30
0
Order By: Relevance
“…It has been widely used in cervical cancer screening. Previous clinical trials have demonstrated that LBC can increase the detection of histologically confirmed neoplastic and preneoplastic diseases while simultaneously decreasing diagnosis of benign processes [11,13,14,15]. In our study, LBC demonstrated smaller cellular clusters with individually scattered tumor cells in the background and more translucent nuclei, making it easier to detect nuclear datails (fig.…”
Section: Discussionsupporting
confidence: 57%
“…It has been widely used in cervical cancer screening. Previous clinical trials have demonstrated that LBC can increase the detection of histologically confirmed neoplastic and preneoplastic diseases while simultaneously decreasing diagnosis of benign processes [11,13,14,15]. In our study, LBC demonstrated smaller cellular clusters with individually scattered tumor cells in the background and more translucent nuclei, making it easier to detect nuclear datails (fig.…”
Section: Discussionsupporting
confidence: 57%
“…In preparing gynaecological cervical smears, several studies have reported that LBC can achieve diagnostic sensitivity equal to that of conventional preparations [13,14,29,30,31]. The first study on LBC for the preparation of buccal epithelial cells was performed by Kujan et al [18], who reported a uniform distribution of cells in addition to improved cytomorphology and visibility of nuclear detail, thereby offering a superior and unbiased sample while controlling cell density, reducing scanty preparations and eliminating air-drying artefacts [13].…”
Section: Discussionmentioning
confidence: 99%
“…LBC offers advantages over the conventional method by providing enhanced slide preparation that produces smears with more homogeneous cell samples and less epithelial cell clumping. Additionally, LBC decreases the amount of mucus, blood and inflammatory compounds [13,14]. To date, LBC has been applied in non-gynaecological procedures such as the diagnosis of small cell lung cancer [15] and fine-needle aspiration cytology of the thyroid gland [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In fact, the LBP method allows variable amount of cells to be stored. 10 The cost of most commercially available LBC systems is extremely expensive and the problem is further compounded by the need for trained individuals and periodic maintenance of the equipments, this is not viable for resource-limited settings. 11,12 Many workers like Alves et al 11 and Lee et al 12 have devised an improved manual method for preparation of LBC smears.…”
Section: Introductionmentioning
confidence: 99%